Performance Characteristics of Diesel Engine Fueled by Biodiesel of Jatropha Oil and Soybean Oil - Malik, Ashish; Kumar, Parlad (Asian Review of Mechanical Engineering, 2012)
Biodiesel is considered as an important renewable and alternative fuel of future. This paper focuses on the performance of biodiesel made from jatropha oil and soybean oil. The biodiesel was produced through transesterification process and it was blended with the fossil diesel. The blended mixtures were tested in an IC diesel engine attached with a dynamometer. On the basis of performance tests it was found that brake thermal efficiency of mixed jatropha and soybean biodiesel blends is nearer to pure diesel oil at different rpm. The brake specific fuel consumption obtained with biodiesel blend of mixture of jatropha and soybean oil is comparable with fossil diesel.